"It's not worth the effort"! Examining service recovery in Airbnb and other homesharing platforms. Issue 9 (10th August 2020) - Mody, Makarand Amrish; Lu, Lu; Hanks, Lydia
Abstract : Purpose: This paper aims to use equity theory to develop and test a model of the dynamics of service recovery in the homesharing context. Design/methodology/approach: Using a sample of those who have experienced a service failure with a homesharing company and have voiced complaints to the company directly, the study adopted alternative model comparison procedures to test three competing models of service recovery and examined the effects of five moderating variables. Findings: The results indicated that the model based on equity theory provides a theoretically and empirically superior explanation of the dynamics of service recovery in the homesharing context than the alternative explanation based on the tenets of justice theory. The two key inputs into the service recovery interaction – consumer complaining and recovery effort and trust in brand – have significant direct effects on post-failure loyalty outcomes, and also significant indirect effects via the mediating mechanism of perceived justice. All five moderators have significant effects for at least one of the post-failure loyalty outcomes. Research limitations/implications: The findings emphasize the company's role in service recovery in the homesharing context. Managers of homesharing platforms need to establish customer service infrastructure that minimizes the amount of time-related, procedural and cognitive effort that customers need to expend in the recovery process, and effect communication that enhances trust in the homesharing brand. Future research is needed on the dynamics of service recovery in alternative hotel-homesharing business models, and on the role of value co-creation in the homesharing context. Originality/value: This study is the first to create a holistic theory-based model of the dynamics of service recovery in the homesharing context, using the novel construct of customer complaining and recovery effort. Also, and contrary to typical conceptualization, it demonstrates the role of trust in brand as an antecedent input into the recovery interaction that can generate loyalty outcomes.